Student Motivation in Scouting Activities at SMP Negeri 20 Padang South - Pratama, Jerry; Nur, Hasriwandi; Johor, Zainul (Yayasan Sekora, 2018)
This study aims to obtain information as well as describe the motivation of students in scouting activities at the 20 Padang Selatan Middle School for the 2017/2018 academic year, with a sample of 30 students of class VII and VIII who actively participate in scouting activities. The research classification is descriptive using the survey method. Data collected through a questionnaire were analyzed with descriptive statistics of frequency tabulation in the form of percentages. The results of research findings in the field are as follows; (1) Intrinsically, students with very high motivation were found to be 6.67%, high 53.33%, medium 20%, low 13.33%, and very low 6.67%. (2) Extrinsically, students with very high motivation were found to be 16.67%, 66.67% high, 10% moderate, 6.67% low, and very low 0.00%. Thus, the conclusion from the findings of this study is that both intrinsically and extrinsically, students have high motivation in scouting activities. For this reason, it is recommended that the teachers / coaches of scouting activities in Junior High School 20 Padang Selatan be professional in increasing activities so as to give birth to a generation that is accomplished, creative and sporty.